Impedance spectroscopy analysis of SnO2 thick-films gas sensors - Ponce, M. A.; Bueno, Paulo Roberto [UNESP]; Varela, José Arana [UNESP]; Castro, M. S.; Aldao, C. M. (Springer, 2008)
A careful analysis of the impedance response of SnO2 thick films under vacuum and air atmosphere is reported in the present work. The AC electrical resistance was analyzed and it was shown that it is highly frequency dependent. Different models and its equivalent circuit representation were proposed and carefully analyzed based on the microstructure features of the device. Basically, an interpretation of the frequency dependent resistance was proposed based on the fact that different grains characteristics and junctions exist. These different grains and junctions are the main source of resistance dependent feature. An equivalent circuit model, considering different grain sizes associated with different grain boundary junctions characteristics, was introduced so that a consistent interpretation of the results was possible.